Serviços ambientais ofertados por diferentes agroecossistemas de base familiar - Martinez, Ernesto Alvaro (2013)
Currently humanity has sought more harmonious processes of social, environmental and economic reproduction to produce goods and services. The approach of Environmental Services has sought to value the benefits that are often imperceptible to society, such as the regulation of gases, scenic beauty, biodiversity conservation, protection of soils, regulation of water functions, food supply, among others. In this context, the family-based agriculture has a key role, presenting itself as a category that can provide an important contribution to this challenge. This study aimed to determine which and how the environmental services offered by agroecosystems from different agricultures contribute to sustainable agricultural development. Through a methodology that predicted the observation of environmental perception of farmers, the characterization of agroecosystems, and even the participatory construction of environmental quality indicators, it was possible to measure the level of supply of these agroecosystems. It was found that different models of family-based agriculture in southern RS, contribute with a good supply of environmental services, as follows: the conservation and improvement of the soil, observed in management practices; the maintenance of biodiversity through the preservation of wild species; regulation of climatic conditions, related to the conservation of areas of natural vegetation, food supply, from a considerable diversity; in addition to the socio-cultural reproduction through customs and traditions related to good relationship with natural resources.